2022
DOI: 10.3390/pharmaceutics14102109
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Silver Nanoparticles Inhibit the Malignant Behavior of Gastric Cancer Cells and Enhance the Therapeutic Effect of 5-Fluorouracil by Promoting Intracellular ROS Generation and Apoptosis

Abstract: (1) Background: Gastric cancer (GC) is the fourth leading cause of cancer death worldwide. Silver nanoparticles (Ag-NPs) have been increasingly used in the diagnosis and treatment of cancer due to their physicochemical properties. This study investigated the role of a kind of biosynthetic silver nanoparticle (b-Ag) in the development of GC, the enhancement of 5-fluorouracil (5F), and its mechanism. (2) Methods: X-ray, transmission electron microscopy (TEM), and UV absorbance were used to detect the characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Additionally, Ca 2+ is closely involved in a bidirectional relationship with ROS generation (33). Several studies showed the capability of AgNPs to induce aberrant ROS production, resulting in the induction of the mitochondrial apoptosis pathway, in different cancer cell lines, including chronic myeloid leukemia, breast, gastric and pancreatic cancer (10,28,(34)(35)(36). We showed that AgNPs induced ROS overproduction in HG-3 cells after 2h-treatment, time at which cell viability was already strongly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ca 2+ is closely involved in a bidirectional relationship with ROS generation (33). Several studies showed the capability of AgNPs to induce aberrant ROS production, resulting in the induction of the mitochondrial apoptosis pathway, in different cancer cell lines, including chronic myeloid leukemia, breast, gastric and pancreatic cancer (10,28,(34)(35)(36). We showed that AgNPs induced ROS overproduction in HG-3 cells after 2h-treatment, time at which cell viability was already strongly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, activation of ATF2 during sorafenib‐induced ferroptosis has been observed, and knockdown of ATF2 was found to promote sorafenib‐induced ferroptosis achieved through the inhibition of SLC7A11 expression mediated by HSPH1, a downstream target of ATF2 124 . Baicalin, a flavonoid derived from Scutellaria baicalensis Georgi , has been demonstrated to enhance the effectiveness of 5‐fluorouracil in GC by promoting ROS‐mediated ferroptosis 161 . Furthermore, STAT3 has been recognized as a modulator of crucial ferroptosis‐related genes, including GPX4 , SLC7A11 , and FTH1 .…”
Section: Ferroptosis In Gcmentioning
confidence: 94%
“…showed that ZnO‐NPs could induce ER stress in mouse ovarian cells through the Keap/Nrf2 signaling pathway and cause apoptosis. Yuan et al 268 . showed that biosynthetic Ag‐NPs inhibited the malignant behavior of gastric cancer cells and enhanced the therapeutic effect of 5‐fluorouracil by promoting intracellular ROS generation and apoptosis.…”
Section: Toxicological Mechanisms Of Npsmentioning
confidence: 99%
“…[263][264][265][266] The study by Xu et al 267 showed that ZnO-NPs could induce ER stress in mouse ovarian cells through the Keap/Nrf2 signaling pathway and cause apoptosis. Yuan et al 268 showed that biosynthetic Ag-NPs inhibited the malignant behavior of gastric cancer cells and enhanced the therapeutic effect of 5-fluorouracil by promoting intracellular ROS generation and apoptosis. Li et al 269 showed that titania-NPs enhanced testicular apoptosis and DNA damage caused by cypermethrin and promoted oxidative stress in testicular tissue.…”
Section: Studies Between Nps and Apoptosismentioning
confidence: 99%